The Effect of Reward Punishment System and Work Culture on Teacher Job Satisfaction - Syahmalini, Syahmalini; Alawi, Dina Kusuma; Ariyadi, Bayu (Development: Studies in Educational Management and Leadership, 2022)
Teacher job satisfaction is one of the incentives for teachers to do their job well to achieve school goals. Of course, in order to educate high-quality students and achieve the goal of running a school, schools must pay attention to the level of teachers' job satisfaction. The purpose of this study was to describe the impact of reward system and work culture on job satisfaction among teachers in SMP Negeri 1 Aceh Tengah. This study used quantitative methods and research design (survey). The population used in this study was teachers from SMP Negeri 1 Aceh Tengah. The techniques used in this study were questionnaires, observations and recordings. The data analysis technique used in this study was multiple regression analysis. The result is shown below: 1). The reward and punishment system has an impact on teachers' job satisfaction, the t value is 3.576, and the t table of 1.683 indicates that 3.576>1.683, then reject Ho and accept h1. 2). Work culture has an impact on teacher job satisfaction, t-count is 3.443, t-table is 1.683, indicating that the value is 3.443>1.683, then reject Ho and accept H1. 3). The reward system and work culture have an impact on teacher job satisfaction, the calculated f value is 16,733, and the f table value is 3.23, indicating that the value 16,733 > 1,683, then Ho rejects and H1 accepts becomes . Therefore, the reward system and work culture had a significant impact on the job satisfaction of SMP Negeri 1 Aceh Tengah teachers.